(untitled) (International Journal of Scientific Pediatrics, 2023)
Resume: An analysis of the literature devoted to the study of the health status of premature newborns born to mothers with preeclampsia is presented. The relationship of preeclampsia with jaundice of premature, underweight children to gestational age, renal pathology, perinatal encephalopathy and maladaptation of the newborn period is discussed. The aim of the study was to study the severity of jaundice in small children born to mothers with preeclampsia, depending on the gestational age and weight of the newborn. Material and methods. The work was carried out at the Department of Pediatrics of the Bukhara Perinatal Center. 44 underweight children born to mothers with preeclampsia, who were divided into 2 groups according to gestational age, were monitored. The first group consisted of 22 premature babies born to mothers with preeclampsia at 22-28 weeks (early prematurity); the second group consisted of 22 premature babies born to mothers with preeclampsia at 29-37 weeks (late prematurity). All newborns underwent general clinical and biochemical analyses (total bilirubin and its fractions, total protein, blood glucose). The severity of jaundice was assessed according to the Kramer scale. The results and their discussion: The results of the analyses showed that in group 1 the average weight of newborns was 872.3g, in the second group 1945.4g of which 4 newborns were diagnosed with intrauterine growth retardation syndrome. In group 1, the maximum level reached up to 246 mmol/l on day 6. The average duration of jaundice was 15 days. In the second group, the maximum level reached up to 209.5 mmol/l and was observed on the 4th-5th day of life. The average duration of jaundice was 12 days. Conclusion. The younger the gestational age and the lower the weight, the higher the bilirubin level and the prolonged course of jaundice.